Fabrication and characterisation of polyethersulfone/chitosan/non-ionic nanofiltration membrane for dyes removal - Johary, F.; Zaimin, F.F.M.; Rohani, R.; Hassan, A.R.; Sharifuddin, S.S.; Isa, M.H.M. (2018)
Recently, dyes are generally used in various industries and release of these dyes into streams will pose a serious threat to the environment. In this research, a nanofiltration membrane was fabricated via phase inversion as it is one of the most convenient methods for membrane fabrication. It is used in removing dyes by using pluronic as a surfactant and chitosan as an additive. By varying the concentration of pluronic as a surfactant at 1 wt%, 2 wt%, and 3 wt%, and a constant amount of chitosan as an additive, three newly dope solutions were formulated. The fabricated membranes were analyzed by evaluating the membrane in terms of pure water permeation (PWP), permeation flux, salts rejection and dyes rejection. The introduction of pluronic as a surfactant and chitosan as an additive to the nanofiltration membrane produced high PWP and presented high salts rejection and dyes removal. Generally, high dyes rejections were achieved by M3 which contained high weight percentage (wt%) of pluronic as it showed highest percentage rejection for acid red, methyl blue and reactive black 5. The functional groups of the membranes were characterized and verified by using Fourier transform infrared spectroscopy (FTIR).